2017
DOI: 10.18466/cbayarfbe.339313
|View full text |Cite
|
Sign up to set email alerts
|

A New Tool for QSPR Researches: ev-degree Randić Index

Abstract: Topological indices have important role in theoretical chemistry for QSPR researches. Among the all topological indices the Randić index has been used more considerably than any other topological indices in chemical and mathematical literature. Most of the topological indices as in the Randić index are based on the degrees of the vertices of a connected graph. Recently novel two degree concepts have been defined in graph theory; ev-degrees and ve-degrees. In this study ev-degree Randić index is defined by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 6 publications
(1 reference statement)
0
18
0
Order By: Relevance
“…The ve-degree, denoted by ξ ve (x 1 ), of any vertex x 1 ∈ V is the number of different edges that are incident to any vertex from the N [x 1 ]. For details see [37]- [41]. We define general ve-degree topological invariant T(G) as follows:…”
Section: V E-degree Topological Descriptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ve-degree, denoted by ξ ve (x 1 ), of any vertex x 1 ∈ V is the number of different edges that are incident to any vertex from the N [x 1 ]. For details see [37]- [41]. We define general ve-degree topological invariant T(G) as follows:…”
Section: V E-degree Topological Descriptorsmentioning
confidence: 99%
“…Zhong and Ediz [36], [37] defined Harmonic index and most of work is done by using classical degree concept. Recently, Chellali et al [38] introduced new degree concepts namely, "ve-degree and ev-degree".…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the ev-degree Zagreb index, the ve-degree Zagreb index, and the ve-degree Randić indices have a better correlation than the Wiener, Zagreb, and Randić indices for predicting certain basic physicochemical properties of octanes. Later, Ediz defined the ev-degree Randić index as R ev (G) � e∈E(G) d ev (e) − (1/2) and show that it gives a better correlation than the Randić index to predict the entropy, acentric factor, and standard enthalpy of vaporization of octanes [25]. Sahin and Ediz [26] have shown that ev-degree and ve-degree Narumi-Katayama indices can be used as potential tools for QSPR analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The classical degree-based frameworks then have been transformed into ve-degree and ev-degree Zagreb and Randic indices in. [29][30][31] The ve-degree Zagreb index has been shown to have a greater predictive ability than the classic Zagreb index.…”
Section: Introductionmentioning
confidence: 99%